Agritourism, Farm Visit, or . . . ? A Branding Assessment for Recreation on Farms. (November 2016) - Barbieri, Carla; Xu, Shuangyu; Gil-Arroyo, Claudia; Rich, Samantha Rozier
The demand and offer of recreational activities on farms has increased over the last decades and promises increased growth in the future because of the benefits it brings to farmers and visitors. Despite this growth, a breadth of names (e.g., agritourism, farm visit) are used interchangeably to depict this activity. Such inconsistency reflects a lack of industry branding which diminishes marketing effectiveness and hinders stakeholders' collaboration. Therefore, a study was conducted to evaluate the Memorability, Distinctiveness, Relevance and Flexibility and overall preference of eight typical names associated with recreation on farms among farmers and visitors. The multimodal approach employed reveals that efforts are needed to standardize and diffuse a brand name for recreation on farms because of reduced Memorability. Although "Agritourism" appears suitable to brand recreation on farms given its Distinctiveness, Relevance, and Flexibility, results are inconclusive and call for further efforts for educating the public about its meaning.